ENHANCING CIVIC EDUCATION LEARNING OUTCOME THROUGH SNAKE AND LADDER LEARNING MEDIA IN MADRASAH IBTIDAIYAH - Zaeni, Abu; Soni Amrullah, Muhammad; Fadilah, Lailatul (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2026)
The lack of variety in Citizenship Education (PKN) learning is the main trigger for the lack of student involvement and enthusiasm in the learning process. This condition then has an impact on low academic achievement, as seen from the average class score that has not reached the Minimum Completion Criteria (KKM). This study was designed to boost the learning achievement of Civic Education (PKN) subjects for grade IV students by utilizing interactive media in the form of snakes and ladders games. This study seeks to answer questions regarding the level of effectiveness of using interactive snakes and ladders media in boosting the Civic Education values ​​of grade IV students at MI Plus Bustanul Ulum. This study applies the Classroom Action Approach (CAR) which is carried out in two stages. This study involved 22 grade IV students as participants. Data were obtained through field observations, written assessments, and official records. The percentage of student learning completion increased significantly, from 45.45% in the pre-cycle stage to 77.27% in the first cycle, and finally reaching 81.81% in the second cycle. Therefore, it can be concluded that the use of interactive snakes and ladders learning media is effective in improving learning outcomes in the Pancasila Education subject for grade IV students of MI Plus Bustanul Ulum.